Physical activity and health - Blair, Steven N.; Bouchard, Claude; Haskell, William L. (Human Kinetics, 2012)
The human body is designed for activity. For most of our history, physical activity was required for survival, but technological advances have eliminated much of the need for hard physical labor. As our activity levels have dropped, it has become clear that a physically inactive lifestyle can lead to a host of health problems. Physical Activity and Health, Second Edition, provides a comprehensive treatment of the research on the benefits of a physically active lifestyle in comparison with the harmful consequences of physical inactivity. Written by leading scientists from the United States, Canada, Europe, and Australia, Physical Activity and Health, Second Edition, brings together the results of the most important studies on the relationship between physical activity, sedentarism, and various health outcomes. The second edition has been fully updated based on the latest advances in this rapidly changing field and expanded to include the following new content: A chapter on the physiology of inactivity and the effects of sedentary behavior even in people who engage in appropriate amounts of physical activity, which is an area of growing interest; More extensive coverage of physical activity, aging, and the brain, including a new chapter on the relationship between physical activity and brain structures and functions; A chapter on the development of national and international physical activity and health guidelines, which will help readers better understand how scientific findings are converted into practical recommendations. Physical Activity and Health, Second Edition, offers a detailed yet concise presentation of key concepts as well as a framework to help readers relate results from single studies or collections of studies to the overall paradigm linking physical activity and physical fitness to health. For each of the topics covered, the text provides an overview of the most important research findings, discusses the limitations of the current knowledge base, and identifies directions for future investigation. At the core of the text is a review of our current understanding of how physical activity affects health concerns such as cardiovascular disease, diabetes, cancer, and obesity as well as aging and mental health. The text identifies sedentary living habits and poor fitness as major public health problems and examines the potential of physical activity to prevent disease and enhance quality of life. This complete resource also looks at the evolution of the field of physical activity and health; variations in physical activity levels across age, sex, and ethnic groups; the body's physiological responses to physical activity; dose-response issues; and the influence of genetics on physical activity, fitness, and health. The book ends with an integration of the issues covered and discusses new opportunities for research. The second edition of Physical Activity and Health continues to offer clear, user-friendly coverage of the most important concepts and research in the field. Numerous special features will aid readers in their comprehension of the material. Chapter outlines and callout boxes help readers key in on important topics and focus their reading, and chapter summaries, definitions of key terms, and study questions provide tools for review and self-testing. Where other books have simply promoted physical activity for the individual or a population, Physical Activity and Health, Second Edition, completely integrates current knowledge of the relationship between physical activity and health. With contributions from some of the finest scientists in the field, this comprehensive text offers information unmatched in accuracy and reliability.